2012
DOI: 10.1016/j.jenvrad.2011.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the 36Cl deposition flux in central Japan: natural background levels and seasonal variability

Abstract: Essential parameters for the applications of 36 Cl as a tracer in groundwater studies include the initial 36 Cl/Cl ratio, at the time of recharge, and/or the natural background deposition flux of 36 Cl in the recharge area. To facilitate the hydrological use of 36 Cl in central Japan, this study aims to obtain a precise estimate of the long-term average local 36 Cl flux and to characterize its seasonal variability. 36 Cl in precipitation was continuously monitored in Tsukuba, central Japan 2 over a period of >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Concentration of 127 I was in the range 0.701-3.43 mg L -1 , with an average of 1.78 ± 0.62 mg L -1 (Fig. 2b), consistent with earlier studies (Aldahan et al, 2009;Xu et al, 2013Xu et al, , 2016, and with a narrower range than reported for Cl - (Tosaki et al, 2012). Periodic changes in 127 I concentrations were insufficient to affect the 129 I/ 127 I ratio, indicating that variations in the ratio were due mainly to 129 I variations (Xu et al, 2013;Fig.…”
Section: Concentrations Of 127 I and 129 I In Rainwatersupporting
confidence: 91%
See 1 more Smart Citation
“…Concentration of 127 I was in the range 0.701-3.43 mg L -1 , with an average of 1.78 ± 0.62 mg L -1 (Fig. 2b), consistent with earlier studies (Aldahan et al, 2009;Xu et al, 2013Xu et al, , 2016, and with a narrower range than reported for Cl - (Tosaki et al, 2012). Periodic changes in 127 I concentrations were insufficient to affect the 129 I/ 127 I ratio, indicating that variations in the ratio were due mainly to 129 I variations (Xu et al, 2013;Fig.…”
Section: Concentrations Of 127 I and 129 I In Rainwatersupporting
confidence: 91%
“…Total monthly deposition of rainwater has been measured since March 2009 on the roof of the Tandem Accelerator Complex building (36.11∞N, 140.10∞E), University of Tsukuba, located ~170 km southwest of the FDNPP, Japan. A funnel-and-bottle collection system was used, with a funnel diameter of 21 cm and a 5 L high-density polyethylene bottle, as described by Tosaki et al (2012). To avoid loss of iodine during storage, rainwater samples were filtered first through glass-fiber filters (Whatman GF/B), then stored with lids in a dark environment until preparation of chemical separation.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Measurements of low‐level 36 Cl concentrations by the accelerator mass spectrometry (AMS) were first adopted for 36 Cl analysis of meteorites, ice cores, or precipitations/water samples to determine ages of meteorites/ice or detect “ 36 Cl bomb pulses” generated by thermonuclear tests in the 1950s (Elmore et al, 1982; Finkel et al, 1980; Nishiizumi et al, 1993; Phillips et al, 1990; Suter et al, 1987; Synal et al, 1990). Later, 36 Cl was measured in precipitation of Israel (Herut et al, 1992), the United States (Hainsworth et al, 1994; Knies et al, 1994), Australia (Keywood et al, 1998), Japan (Tosaki et al, 2012), across the Europe (Johnston & McDermott, 2008; Pupier et al, 2016; Santos et al, 2004), and at other places around the planet (Scheffel et al, 1999). Moysey et al (2003) explored the nationwide 36 Cl/Cl ratios of meteoric groundwater to show the spatial patterns of meteoric 36 Cl/Cl ratio across the United States.…”
Section: Introductionmentioning
confidence: 99%